Level of speaking and oral test-taking anxieties experienced by university students - Yusof, Nurkarimah (2014)
This study was conducted by using both quantitative and qualitative approaches to investigate the issues of speaking and oral test-taking anxiety among the ESL university students. It is concerned with measuring anxiety of the students with regard to speaking skills and taking an oral test. Specifically, it investigates the relationship between the students‟ speaking anxiety in English, speaking test anxiety and their speaking test performance. Quantitative data was gathered through a survey questionnaire administered to 900 final year undergraduate students across disciplines who sat for a speaking test. The survey questionnaire was adapted from the FLCAS (Foreign Language Classroom Anxiety Scale) developed by E. K.Horwitz, Horwitz and Cope (1986). Both descriptive and inferential statistics (Pearson‟s correlation coefficient analysis and independent sample t-test) were employed to analyse the data. The findings from the survey questionnaire suggested that the majority of the students generally experienced a moderate level of speaking anxiety and speaking test anxiety. Findings from the correlational analysis revealed that speaking anxiety holds a positive, high, and significant relationship with speaking test anxiety in English. Moreover, speaking anxiety and speaking test anxiety were also found to have a significant but negative relationship with the students‟ speaking test performance which suggests that if the anxiety level increases, the speaking test performance may decrease. Findings from the independent sample t-test analysis showed no significant differences were found between the students‟ speaking anxiety and speaking test anxiety with gender. This indicates that female and male students experienced similar levels of speaking anxiety and speaking test anxiety in English. A semi-structured interview was also conducted with seven experienced language instructors to investigate their perceptions on the issues of speaking anxiety and speaking test anxiety among the ESL learners. The interview sessions were conducted around 20-30 minutes each and were audio recorded with the consent of each interviewee. The responses from each interview sessions were then transcribed,summarized, and categorized in terms of the major themes that can capture notions on “anxiety about learning a second language”, “anxiety towards speaking in the second language”, and “anxiety towards taking a speaking test in English”. Coding,labelling and categorizing was also done to further organize and analyse the interview data. Findings from the interview data showed that most of the instructors were aware of the issues pertaining to speaking and oral test-taking anxiety along with their role in helping the students to cope with anxiety. However, several issues were raised, such as their lack of ability to differentiate the manifestations of anxiety showed by the students. Findings from both the survey questionnaire and interview also found that speaking skills were the most anxiety-provoking for the students compared to the other language skills.